Mediating roles of meaning in life and psychological flexibility in the relationships between occupational stress and job satisfaction, job performance, and psychological distress in teachers - Yildirim, Murat; Dilekçi, Ümit; Manap, Abdullah (Frontiers in Psychology, 2024)
Funding: The authors received no financial support for the research, authorship, and/or publication of this article Ethical approval: All procedures performed in studies involving human participants were in accordance with the ethical standards of the institutional and/or national research committee and with the 1964 Helsinki Declaration and its later amendments or comparable ethical standards. The research protocol received approval from the Ethics Committee of Batman University in Türkiye (2023/05-07).Informed consent: Consent was obtained from all participants included in the study.The data supporting this study's findings are available from the corresponding author, [MY], upon reasonable request.